Etnobotani Tumbuhan Beluntas (Pluchea Indica) sebagai Tanaman Obat di Kampung Bojong Salam, Kecamatan Banyuresmi Garut - Hilwa Kamilatunnuha; Tri Cahyanto (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
This study discusses the use of beluntas plants (Pluchea indica) as medicinal plants in Bojong Salam Village, Banyuresmi District, Garut. Ethnobotany investigates the interaction between people and plants, particularly in the context of traditional medicine. The people of Bojong Salam Village have long used beluntas plants as medicine to treat body odor, bad breath, back pain, and vaginal discharge. This study involved interviews with 30 respondents using a purposive sampling method. In data analysis, quantitative and qualitative approaches were used, including calculating the Use Value (UV) and Fidelity Level Index (FIC). The results showed that beluntas leaves had the highest UV value of around 0.5 and FIC of around 50% as a medicine for vaginal discharge, followed by other benefits as a medicine to eliminate body odor, bad breath and back pain. The results showed that beluntas is an important plant in traditional medicine used by the people of Bojong Salam Village.